Beyond TRIPS: Reconstructing Communal Intellectual Property Law in Indonesia through Human Rights and Criminal Enforcement - Annas, Gilang Kresnanda; Baskoro, Aji; Witro, Doli; Izzuddin, Washif (Faculty of Law, Jambi University, 2026)
This article examines the structural vulnerabilities in the legal protection of Communal Intellectual Property in Indonesia, focusing on ownership claims, misappropriation, and the limited effectiveness of enforcement mechanisms. While existing scholarship has primarily addressed CIP through intellectual property and human rights perspectives, limited attention has been given to the intersection of doctrinal inconsistencies, weak enforcement, and the absence of criminal law mechanisms. This study employs a doctrinal legal research methodology, integrating statutory, conceptual, historical, and comparative approaches, supported by qualitative analysis. The findings identify three interrelated challenges. First, Indonesia’s CIP regime, influenced by the TRIPS framework, reflects an individualistic and economically oriented paradigm that is incompatible with the collective and intergenerational nature of indigenous knowledge. Second, a persistent doctrinal tension positions the state as the formal rights-holder, thereby weakening the legal standing and autonomy of indigenous communities. Third, the absence of explicit criminal provisions addressing misappropriation, biopiracy, and unauthorized commercialization creates a significant enforcement gap that undermines deterrence and enables continued exploitation. This article argues that violations of CIP should be reconceptualized not merely as economic infringements but as violations of cultural rights and human dignity. It further highlights the lack of criminal accountability as a critical weakness in the current legal framework. By incorporating recent developments in Indonesian criminal law, including the recognition of living law and corporate criminal liability, this study proposes a reconstruction of the CIP regime through a sui generis approach that integrates human rights principles with criminal enforcement to strengthen protection and ensure equitable benefit-sharing